Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1161/circheartfailure.118.005371
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variation in RBM20 Causes a Highly Penetrant Arrhythmogenic Cardiomyopathy

Abstract: Background: Variants in the cardiomyocyte-specific RNA splicing factor RBM20 have been linked to familial cardiomyopathy but the causative genetic architecture and clinical consequences of this disease are incompletely defined. Methods and Results: To define the genetic architecture of RBM20 cardiomyopathy, we first established a database of RBM20 variants associated with cardiomyopathy and compared these to variants observed in the general population with respect to their location in the RBM20 coding transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
111
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(121 citation statements)
references
References 27 publications
0
111
0
5
Order By: Relevance
“…Also associated with a higher risk of arrhythmic events are mutations in the FLNC gene, which encodes filamin proteins; the RNA-binding motif protein 20 gene (RBM20 gene), which encodes a protein that regulates splicing and the phospholamban (PLN) gene, which encodes a protein that inhibits a sarcoplasmic ATPase [21,27]. In a 2019 study, it was demonstrated that RBM20 mutation carriers were more likely to have NSVT and sustained VT than idiopathic DCM cohorts [28]. The AR-DCM phenotype is associated with a high risk of fatal arrhythmias.…”
Section: Mutations Associated With Scdmentioning
confidence: 99%
“…Also associated with a higher risk of arrhythmic events are mutations in the FLNC gene, which encodes filamin proteins; the RNA-binding motif protein 20 gene (RBM20 gene), which encodes a protein that regulates splicing and the phospholamban (PLN) gene, which encodes a protein that inhibits a sarcoplasmic ATPase [21,27]. In a 2019 study, it was demonstrated that RBM20 mutation carriers were more likely to have NSVT and sustained VT than idiopathic DCM cohorts [28]. The AR-DCM phenotype is associated with a high risk of fatal arrhythmias.…”
Section: Mutations Associated With Scdmentioning
confidence: 99%
“…RBM20 was itself first identified in a search for a familial genetic basis of DCM in human patients (Brauch et al, 2009). Subsequent investigation has identified additional patients and mutations involving RBM20 related to DCM (Zhao et al, 2015b;Long et al, 2017;Wells et al, 2013;Waldmüller et al, 2015;Chami et al, 2014;Refaat et al, 2012;Rampersaud et al, 2011;Millat et al, 2011;Li et al, 2010;Robyns et al, 2019), as well as cardiac arrhythmia (Nielsen et al, 2018;Parikh et al, 2019), pediatric restrictive cardiomyopathy (Rindler et al, 2017) and left-ventricular non-compaction . Although representing only 3 % of idiopathic cases, patients with DCM that have mutant RBM20 correlate with earlier disease onset, high penetrance, and requirement for heart transplantation (Brauch et al, 2009;Li et al, 2010;Kayvanpour et al, 2017;Wells et al, 2013;Hey et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…RBM20 is composed of two zink finger domains, one RNA‐recognition motif (RRM)‐type RNA binding domain and an arginine‐/serine‐(RS)‐rich region. In 2019, two mutational hot spot regions in exons 9 and 11 of RBM20 have been recognized 26 . The majority of pathogenic RBM20 mutations is localized in the RS domain 11,18,19,23 .…”
mentioning
confidence: 99%
“…In 2019, two mutational hot spot regions in exons 9 and 11 of RBM20 have been recognized. 26 The majority of pathogenic RBM20 mutations is localized in the RS domain. 11,18,19,23 Nevertheless, a global understanding of variant pathogenicity across the RBM20-coding transcript remains elusive.…”
mentioning
confidence: 99%
See 1 more Smart Citation